(SVXRL[FLA OAKJOAXLMJV APANYVF]V XRORV A (B/ (SELAZRULMRV NRDLVORV SRNN]P OFXABNJX]Ps - (SDf}ugca(Sprsrynrw Df}ugc(Slrw Os ((SAefnzrl Myulga(Smlej(B,s, 1991)
(SVJOFLA VXR []UR R ELAPYVOAXLMRV []URV FV]XFULMR DLPROFPR MAL OFXUR ELAPYVOAXRV ELAPYVOAXLMR MAL OLMXR DLPROFPR VXRP []UR FYKFLA MAL FSLSFER AVMJVFLV ELAPYVOAXLMFV VYPAUXJVFLV (B& (SMAOSYNFVs